Răspuns:
Explicație pas cu pas:
[tex]3x^{2}[/tex] =(15-[tex]3\sqrt{3}[/tex])×[tex]\sqrt{28-10\sqrt{3} }[/tex]
[tex]3x^{2}[/tex] =(15-[tex]3\sqrt{3}[/tex])×(5-[tex]\sqrt{3}[/tex])
[tex]3x^{2}[/tex] =75-[tex]30\sqrt{3}[/tex]+3[tex](\sqrt{3} )^{2}[/tex]
[tex]3x^{2}[/tex] =75-[tex]30\sqrt{3}[/tex]+3×3
[tex]3x^{2}[/tex] =75-[tex]30\sqrt{3}[/tex]+9
[tex]3x^{2}[/tex] =84-[tex]30\sqrt{3}[/tex]
[tex]\frac{3x^{2} }{3}[/tex] = [tex]\frac{84-30\sqrt{3} }{3}[/tex]
[tex]x^{2}[/tex] =28-[tex]10\sqrt{3}[/tex]
x={5-[tex]\sqrt{3}[/tex], [tex]\sqrt{3}[/tex]-5}
Sper ca te am ajutat :)